Combination treatment of trans-arterial chemo-embolisation, radiotherapy and hyperthermia (CERT) for hepatocellular carcinoma with portal vein tumour thrombosis: Interim analysis of prospective phase II trial. (2nd April 2016) - Yu, Jeong Il; Park, Hee Chul; Oh, Dongryul; Noh, Jae Myoung; Jung, Sang Hoon; Kim, Hye Yeong; Shin, Sung Wook; Cho, Sung Ki; Sinn, Dong Hyun; Paik, Yong-Han; Gwak, Geum-Youn; Choi, Moon Seok; et al.
Abstract: Objectives This study evaluated the objective response to and toxicity of trans-arterial chemo-embolisation (TACE) followed by radiotherapy and hyperthermia (CERT) in hepatocellular carcinoma patients with portal vein tumour thrombosis.Methods The study design was a single-centre prospective phase II trial. Patients were first treated with TACE, with the first hyperthermia session 1 week later. Respiration-gated radiotherapy (RT) was delivered in 10 fractions of 3–5 Gy after another week. Six sessions of hyperthermia were delivered twice a week according to an energy escalation protocol. Response evaluation was planned at 1 month after RT completion using the modified Response Evaluation Criteria in Solid Tumors (RECIST). Toxicity was determined using the Common Terminology Criteria for Adverse Events (CTCAE) version 4.0.Results Interim analysis was conducted on patients enrolled from October 2013 to November 2014. During this period, 46 patients (90.2%) who received at least one hyperthermia session were eligible and enrolled. Median follow-up was 6.7 months (range 2.0–15.0 months). Complete response was observed in 10 (21.7%) patients and partial response in 27 (47.8%). Most toxicities were grade I or II. One death was related to severe pneumonia of unknown cause in the left lung and one patient could not complete planned treatment because of continuous elevation of bilirubin after TACE. Late, asymptomatic gastroduodenal toxicities were noticed in 13 (28.3%) patients.Conclusion Preliminary evaluation of CERT showed a promising response rate with acceptable toxicities.